Pharmacist's interventions in factors contributing to medication errors reduces medication errors in self-management of patients in the rehabilitation ward - Ryohei Suzuki; Takako Uchiya; Takamasa Sakai; Masaaki Takahashi; Fumiko Ohtsu (BMC, 2022)
Abstract Background The number of medications, number of administrations per day, dosing frequency on indicated day, and medication from multiple prescriptions are the medication factors prone to medication errors in self-management that have been previously reported. However, whether pharmacists actually intervene in medication factors that affect medication error occurrences in self-management is unclear. Therefore, we conducted this study to clarify these issues. Method This study included patients who underwent self-management in the rehabilitation ward of Higashinagoya National Hospital. From April 2019 to March 2020, a one-pharmacist period existed, and from April 2020 to March 2021, a two-pharmacist period existed. The number of patient instructions and interventions were expected to increase with an increase in the number of pharmacists. Considering this to be an environment of differential interventions by pharmacists, a pre-post-test design was conducted with all self-managed patients in both the time periods. The primary and secondary endpoints were the proportion of medication error occurrences and proportion of pharmacist's interventions in medication factors, respectively. Result The proportions of medication error occurrences during the one-pharmacist and two-pharmacist periods were 41% (71/173) and 28% (51/180) (relative risk 0.690, 95% confidential interval 0.515-0.925), respectively. The proportion of pharmacist's interventions in medication factors in the one-pharmacist period was 13% (22/173) and 22% (40/180) in the two-pharmacist period; there was an increase in the proportion of pharmacist's interventions in medication factors in the two-pharmacist period. Conclusion The proportion of medication error occurrences was significantly lower in the two-pharmacist period than that in the one-pharmacist period. This can be attributed to the increase in the proportion of pharmacist's interventions in medication factors. Therefore, an environment in which pharmacists could intervene in the medication factors to prevent medication errors in advance is necessary.